(untitled) (Pulse, 2025)
Background: Common bile duct (CBD) stones are a potentially serious complication of gallstone disease, requiring timely removal to prevent life-threatening sequelae. Endoscopic retrograde cholangiopancreatography (ERCP) is the standard of care, but challenging anatomical variations—such as a periampullary diverticulum—can make biliary cannulation extremely difficult or impossible with standard techniques. Case Presentation: We report the case of a 28-year-old female doctor who developed severe sepsis and hepatic microabscesses following a laparoscopic cholecystectomy which was complicated by retained CBD stones. Initial ERCP attempts failed due to an intradiverticular papilla hidden within a large periampullary diverticulum. At Evercare Hospital Dhaka, after hemodynamic stabilization, a novel clip-assisted technique was employed. By applying a hemoclip to the edge of the diverticulum, the papilla was repositioned, enabling successful CBD cannulation, sphincteroplasty, and complete stone extraction with stent placement. The patient’s liver function and sepsis parameters improved rapidly, and she achieved a full recovery. Conclusion: This case demonstrates the life-saving potential of innovative endoscopic techniques in managing complex biliary anatomy. To our knowledge, this is the first reported use of clip-assisted papilla repositioning for ERCP in Bangladesh, underscoring the importance of advanced skills, creativity, and multidisciplinary expertise in overcoming procedural challenges. Pulse Vol.17, 2025 P: 29-32